Modelling the environmental, social, and economic implications of using fruit pomace as an alternative livestock feed resource: a system dynamic modelling approach - Bakasa, Clinton (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScFoodSc)--Stellenbosch University, 2022.